An Excel tool for deriving key photosynthetic parameters from combined gas exchange and chlorophyll fluorescence: theory and practice. (30th June 2015) - Bellasio, Chandra; Beerling, David J; Griffiths, Howard
Abstract: Combined photosynthetic gas exchange and modulated fluorometres are widely used to evaluate physiological characteristics associated with phenotypic and genotypic variation, whether in response to genetic manipulation or resource limitation in natural vegetation or crops. After describing relatively simple experimental procedures, we present the theoretical background to the derivation of photosynthetic parameters, and provide a freely available Excel‐based fitting tool (EFT) that will be of use to specialists and non‐specialists alike. We use data acquired in concurrent variable fluorescence–gas exchange experiments, where A / C i and light–response curves have been measured under ambient and low oxygen. From these data, the EFT derives light respiration, initial PSII (photosystem II) photochemical yield, initial quantum yield for CO2 fixation, fraction of incident light harvested by PSII, initial quantum yield for electron transport, electron transport rate, rate of photorespiration, stomatal limitation, Rubisco (ribulose 1·5‐bisphosphate carboxylase/oxygenase) rate of carboxylation and oxygenation, Rubisco specificity factor, mesophyll conductance to CO2 diffusion, light and CO2 compensation point, Rubisco apparent Michaelis–Menten constant, and Rubisco CO2 ‐saturated carboxylation rate. As an example, a complete analysis of gas exchange data on tobacco plants is provided. We also discuss potential measurement problems and pitfalls, and suggest how such empirical data could subsequently be used to parameterize predictive photosynthetic models. Abstract : We review the theory of gas exchange data analysis and present a freely downloadable Excel‐based fitting tool (EFT) to derive a comprehensive suite of physiological parameters. These allow detailed comparison of photosynthetic characteristics to be made, for natural vegetation, plants with engineered photosynthetic traits, or to distinguish between C3, C4, C2, or intermediate metabolism. We include a practical example, a detailed gas‐exchange protocol and a link to a video tutorial.